Legal Regulations on Gold Banks Post-UUP2SK and POJK17/2024: Normative Review and Comparison with International Practices - George Yudistira Irawan; Hwian Christianto (International Journal Labs, 2025)
This article analyzes the legal framework for Indonesia’s bullion bank following the enactment of the Financial Sector Development and Strengthening Act of 2023 (UUP2SK No. 4/2023) and the Financial Services Authority Regulation No. 17/2024 (POJK17/2024). It also comparatively reviews gold banking regulations and practices in other countries to derive lessons for Indonesia. The research employs a normative juridical method, relying on primary legal sources (legislation and official regulations) and secondary sources (academic literature). The study indicates that UUP2SK formally recognizes bullion banking as a financial business activity related to gold, mandating Financial Services Authority (OJK) licensing for any institution engaging in such business. In response, POJK17/2024 establishes a comprehensive regulatory framework governing bullion bank operation, including the scope of activities (gold deposit-taking, financing, trading, custodial services, etc.), licensing procedures, capital requirements, and prudential principles. Internationally, countries like Turkey and Malaysia have successfully integrated gold banking into their financial systems—Turkish banks offer digital gold deposit accounts, and Malaysian banks provide online gold investment services under central bank oversight. Indonesia can learn from these experiences by enhancing public literacy, ensuring regulatory transparency, and building trust in gold-based financial products. With a robust legal framework in place and the first bullion bank licenses granted to state-owned Pegadaian and Bank Syariah Indonesia, Indonesia’s nascent gold banking sector holds significant promise. However, further refinement (i.e., clarifying tax treatment and strengthening consumer protection) is needed to optimize the implementation of the national bullion bank and to harness its potential for financial inclusion and economic growth.